Active health Ombudsman service: evaluation of the quality of delivery and birth care - Karlo Jozefo Quadros de Almeida; Francis Nakle de Roure; Roberto José Bittencourt; Regina Maria Dias Buani dos Santos; Fernanda Viana Bittencourt; Leila Bernarda Donato Gottems; Fábio Ferreira Amorim (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To evaluate the active health Ombudsman service as an instrument to evaluate the quality of delivery and birth care in the Cegonha Network of the Federal District of Brazil. METHODS This is a cross-sectional study of the telephone survey type carried out with 1,007 mothers with deliveries between October 15, 2013 and November 19, 2013 in the twelve public maternity hospitals that make up the Cegonha Network of the Federal District of Brazil. The instrument has 25 multiple choice or Likert scale questions, including sociodemographic data and acceptability evaluation in five domains: accessibility, relationship between the patient and health professionals, conditions of the structure of the service, information to the patient, and equity and opinion of the patient. We have studied qualitative or categorical variables according to the frequency and distribution of proportions. We have used the score transformed into a scale from zero to 100 for the analysis of the Likert-type scale questions. Results have been expressed as mean and standard deviation. RESULTS Access to prenatal appointments was evaluated as good or excellent by 86.1% of the participants and laboratory tests was evaluated as good or excellent by 85.2% of them. The access to imaging tests was evaluations as good or excellent by 45.7% of the women; 79.5% of the interviewees had their delivery in the maternity hospital where they sought initial care and 18.3% received a home visit by a community health agent after discharge. Most women reported that newborns were placed skin-to-skin immediately after birth, 48.9% had a companion at the time of the delivery, 76.3% were advised about the first appointment of the newborn, and 94.8% were advised on breastfeeding in the maternity hospital. Regarding the evaluation of health professionals, 85.9% of the women considered reception and cordiality as good or excellent at the prenatal care and 94.8% considered it as good or excellent at the maternity hospital. CONCLUSIONS The active health Ombudsman service has contributed to evaluate the quality of public management by allowing the incorporation of the perspective of users of the health service in the evaluation of the acceptability of the Cegonha Network in the Federal District of Brazil.